Analisis Pengaruh Pengungkapan Lingkungan, Sosial dan Tata Kelola (ESG) Terhadap Return Saham dengan Kepemilikan Manajerial Sebagai Moderasi - Graita Nur Fajrin; Ratna Anggraini; Gentiga Muhammad Zairin (Teewan Journal Solutions, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on stock returns, with managerial ownership as a moderating variable, in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange. The data used are secondary data obtained from annual reports and sustainability reports for the period 2021–2023, covering a total of 42 companies and 126 observations. The analysis method employed is panel data regression using EViews 13 software. The results indicate that ESG disclosure and governance disclosure do not have a significant effect on stock returns. However, environmental disclosure has a positive effect, while social disclosure has a negative effect on stock returns. Moreover, managerial ownership does not moderate the relationship between ESG disclosures and stock returns. These findings suggest that the market has not fully integrated sustainability considerations into stock performance evaluations in the observed sector, and that managerial ownership does not significantly strengthen the effect of ESG disclosure on stock returns.